E-commerce Mobile Solution for Retailers - Vieira, Leandro Almeida (2021)
Today, it is almost impossible to not have a mobile application directed for any type of business. More and more people own mobile phones and these devices are the main form of interaction with businesses like banks or retailers. If the user experience in these applications is bad, or inexistent, a user will have no problem in looking for a substitute in the thousands of applications available for download. Users also want a consistent experience on whatever device they are using, let it be on Android, iOS, or a desktop computer. Isobar provides a client with an application directed for retailers. These retailers use it to interact with customers and make purchases or refunds on their behalf. However, this application is only available for iOS devices, which limits the number of users for the application. For this reason, the development of a new application was proposed. This application will do everything that the old one could do, but it will have support across multiple platforms – iOS, Android, and a browser version for other devices. This report describes all the work during the development of this application at Isobar.